Pyridoxine Dependent Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Four children with pyridoxine dependent seizures beginning at 2 to 19 months are reported from the Loyola University Medical Center, Maywood, IL.